2022
DOI: 10.2196/28621
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Korean Version of the Health Information Technology Usability Evaluation Scale: Psychometric Evaluation

Abstract: Background Rigorous development of mobile technologies requires the use of validated instruments to evaluate the usability of these tools, which has become more relevant with the expansion of these technologies. Although various usability evaluation tools have been developed, there are relatively few simple evaluation instruments that have been validated across diseases and languages in mobile health (mHealth) information technology for use in multiple diseases. Ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…The Health-ITUES is structured around four subdomains: (1) impact, (2) perceived usefulness, (3) perceived ease of use, and (4) user control. In the research conducted by Lee and Schnall [39], Cronbach α coefficient was determined to be .951, whereas in this study, it was found to be .967.…”
Section: Health It Usabilitycontrasting
confidence: 59%
See 1 more Smart Citation
“…The Health-ITUES is structured around four subdomains: (1) impact, (2) perceived usefulness, (3) perceived ease of use, and (4) user control. In the research conducted by Lee and Schnall [39], Cronbach α coefficient was determined to be .951, whereas in this study, it was found to be .967.…”
Section: Health It Usabilitycontrasting
confidence: 59%
“…The Health-ITUES, previously deployed among adult users and medical professionals [ 38 ], was used in its Korean adaptation, the Korean Health-ITUES, as translated by Lee and Schnall [ 39 ]. The Health-ITUES is structured around four subdomains: (1) impact, (2) perceived usefulness, (3) perceived ease of use, and (4) user control.…”
Section: Methodsmentioning
confidence: 99%
“… 33–35 The survey has shown construct and predictive validity through confirmatory factor analysis, exploratory factor analysis, and structural equation modeling by the tool’s creators and has been externally validated in multiple use cases. 34 , 36 , 37 Prior to the study, the pharmacists were instructed on the proper use of the paper version of the Health-ITUES. After each simulated encounter, the pharmacists completed a Health-ITUES survey.…”
Section: Methodsmentioning
confidence: 99%
“…Third, the assessment of participants' learning outcomes, based on the educational methods of PDFs and videos, was carried out using four items inspired by Jeong [24] and ve items related to sexual knowledge and satisfaction with sex and menstruation education by Ho [16] Finally, The usability of the PDF and video education methods was evaluated by the Korean version of the Health Information Technology Usability Evaluation Scale (Korean Health-ITUES), consisting of 20 items [25]. All items are structured using a Likert scale.…”
Section: Effects Of Student-led Sex and Menstruation Education About ...mentioning
confidence: 99%